Paris 1928 : Nexus II - Miller, Henry, 1891-1980 (Miller, Henry, 1891-1980. Rosy crucifixion., 2012)
During the Great Depression, Henry Miller travels to Paris and around Europe with his wife "Mona" (June Miller), and documents his sexual exploits and relationship with his spouse.